NEW DATA ON CRUSTAL STRUCTURE AT DEPTH UNDER THE CENTRAL PART OF THE KURILE-KAMCHATKA ISLAND SYSTEM - Sergeyev K.F.; Anosov G.I.; Petrov A.V.; Argentov V.V. (My University, 1988)
In 1983 and 1984 we ran deep seismic sounding and correlation-refraction shooting surveys in the central part of the Kurile-Kamchatka island system, which allowed us for the first time to directly determine the crustal thickness here and modify the idea of its underestimated value. These observations were made near Simushir Island on two profiles, transverse and longitudinal relative to the trend of the island-arc uplift. The results are shown as seismic crustal sections of which the most representative is the one along the transverse profile. The most persistent seismic boundary along this profile is one with a constant boundary velocity (8.2 km·s-1), as calculated from refracted waves recorded at the farthest possible distances (≤190 km).